Morphological study of nymphal stages in Tenodera fasciata (Olivier, 1792) (Mantodea: Mantidae) - Oshima, Kazuyuki (Zootaxa, 2022)
To date, no accurate identification method has been established for distinguishing mantis species of the genus Tenodera at all instar nymphal stages. In this paper, all instar nymphal stages of Tenodera fasciata (Olivier, 1792) are described in detail. This is the first step toward establishing an identification method for distinguishing the species from other members of the genus, particularly, T. angustipennis Saussure, 1869, which is sympatric with T. fasciata in Japan. Morphological differences between instars in nymphal stages, and between male and female in nymphal stages, were found. However, there was no difference between male and female 1st instars. Sex in nymphal stages are identified by the presence or absence of a crack at the posterior margin of the abdominal sternite IX between immature gonoplacs, the shape of the posterior margin of the sternites VII and IX, the occurrence of gonapophyses on the sternite VIII, and so on. Instars in nymphal stages are identified by body length, the length of discoidal spines of the profemur, the shape and size of the wing pads, the shape of abdominal sternite VII to IX, and so on.